A 3-methylcrotonyl-CoA carboxylase deficient human skin fibroblast transcriptome reveals underlying mitochondrial dysfunction and oxidative stress. (September 2016) - Zandberg, L.; van Dyk, H.C.; van der Westhuizen, F.H.; van Dijk, A.A.
Abstract: Isolated 3-methylcrotonyl-CoA carboxylase (MCC) deficiency is an autosomal recessive inherited metabolic disease of leucine catabolism with a highly variable phenotype. Apart from extensive mutation analyses of the MCCC1 and MCCC2 genes encoding 3-methylcrotonyl-CoA carboxylase (EC 6.4.1.4), molecular data on MCC deficiency gene expression studies in human tissues is lacking. For IEMs, unbiased ⿿-omics⿿ approaches are starting to reveal the secondary cellular responses to defects in biochemical pathways. Here we present the first whole genome expression profile of immortalized cultured skin fibroblast cells of two clinically affected MCC deficient patients and two healthy individuals generated using Affymetrix ® HuExST1.0 arrays. There were 16191 significantly differentially expressed transcript IDs of which 3591 were well annotated and present in the predefined knowledge database of Ingenuity Pathway Analysis software used for downstream functional analyses. The most noticeable feature of this MCCA deficient skin fibroblast transcriptome was the typical genetic hallmark of mitochondrial dysfunction, decreased antioxidant response and disruption of energy homeostasis, which was confirmed by mitochondrial functional analyses. The MCC deficient transcriptome seems to predict oxidative stress that could alter the complex secondary cellular response that involve genes of the glycolysis, the TCA cycle, OXPHOS, gluconeogenesis, β-oxidation and the branched-chain fatty acid metabolism. An important emerging insight from this human MCCA transcriptome in combination with previous reports is that chronic exposure to the primary and secondary metabolites of MCC deficiency and the resulting oxidative stress might impact adversely on the quality of life and energy levels, irrespective of whether MCC deficient individuals are clinically affected or asymptomatic.